Politik Dan Kebijakan Pendidikan Agama Islam Berbasis Multikultural Menuju Pendidikan Agama Islam Yang Ideal Di Indonesia - Putra, Muhammad Iman (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2023)
The transformation of Islamic education plays an important role in responding to the personal interests of decision makers in shaping national education policy. the political dimension of learning, recognizing the authority of the state in educational matters, and recognizing the relationship between political relations and Islamic education policy. The research method used is literature research by collecting data from articles (knowledge) related to the topic discussed, namely the multicultural religious education system. The data researchers took from literature in the form of books, research journals, and supporting articles. The results of research have a relationship between learning and politics that is a close and dynamic relationship, Education is considered an important field for the purpose of existence of the creation of programs and processes that formulate, compile and produce the expected results. Then there was a reform period policy on Islamic education, namely through madrasah, dayah, surau, and pesantren educational institutions. The politics and policies of multicultural-based Islamic religious education through decision-making processes related to special education are shaped by the formulation of the National Education System Law, which in turn takes into account the practices and teachings of Islamic educational institutions. By putting forward realistic curricula, interpretations, moral values, procedures and skills that both achieve the desired educational goals possessed by the younger generation.